2013
DOI: 10.1016/j.celrep.2012.11.025
|View full text |Cite
|
Sign up to set email alerts
|

Yeast Endosulfines Control Entry into Quiescence and Chronological Life Span by Inhibiting Protein Phosphatase 2A

Abstract: The TORC1 and PKA protein kinases are central elements of signaling networks that regulate eukaryotic cell proliferation in response to growth factors and/or nutrients. In yeast, attenuation of signaling by these kinases following nitrogen and/or carbon limitation activates the protein kinase Rim15, which orchestrates the initiation of a reversible cellular quiescence program to ensure normal chronological life span. The molecular elements linking Rim15 to distal readouts including the expression of Msn2/4- an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
110
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(129 citation statements)
references
References 28 publications
15
110
0
4
Order By: Relevance
“…Although Msn2/4 and Gis1 have redundant functions by sharing many common targets, our study has revealed that Msn2, but not Gis1, is a direct substrate of Rim15. The kinase activity of Rim15 has been shown to be necessary for the Gis1-dependent transcription [20], but Rim15 may contribute to the activation of Gis1 through indirect pathway involving Igo1/2 and PP2A CDC55 [16]. Furthermore, we have shown that Rim15 can activate Hsf1 by direct phosphorylation.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…Although Msn2/4 and Gis1 have redundant functions by sharing many common targets, our study has revealed that Msn2, but not Gis1, is a direct substrate of Rim15. The kinase activity of Rim15 has been shown to be necessary for the Gis1-dependent transcription [20], but Rim15 may contribute to the activation of Gis1 through indirect pathway involving Igo1/2 and PP2A CDC55 [16]. Furthermore, we have shown that Rim15 can activate Hsf1 by direct phosphorylation.…”
Section: Discussionmentioning
confidence: 72%
“…In agreement with the fact that Rim15 is an upstream regulator of Igo1/2, the triple mutant rim15Digo1Digo2D and rim15D showed similar levels of BTN2 and HSP26 expression, which were slightly lower than those in igo1Digo2D. Since Gis1 activity has been shown to be regulated by Igo1/2 via PP2A CDC55 [16], we checked whether Gis1 is involved in BTN2 mRNA expression. However, glucose starvation-dependent induction of BTN2 was not affected by the lack of GIS1 (Fig 3B).…”
Section: Btn2 Mrna Level Is Regulated By Igo1/2 Upon Glucose Starvationmentioning
confidence: 88%
See 2 more Smart Citations
“…So identification of the PP1 regulatory subunit(s) for Gwl inactivation is very important for cell cycle control. This kinase-phosphatase balancing mechanism composed of Gwl, ARPP/ENSA, PP2A-B55 and PP1 is probably broadly utilized as a functional unit, although a partner kinase, corresponding to CDK, might be different in each case, because PP2A-B55 plays versatile roles in many other biological phenomena, where mitotic CDK not believed to be operating (for example, in the nutrient response in budding yeast [10]). We see this as a useful plug-in module whenever switch-like changes in phosphorylation states are required in Nature.…”
mentioning
confidence: 99%